Attitude to Behavior of Buying Life Insurance in Viet Nam - Thi Huong Mai; Bich Hong Hoang (International Journal of Small and Medium Enterprises and Business Sustainability, 2020)
Life insurance is a civilized foundation of a country. The value of insurance products is becoming more and more useful over time and is the basis for a comprehensive social security ensuring. However, despite the values and benefits of these products, people's attitudes towards life insurance are still disinterested. This study aims to quantify people's attitudes towards life insurance in Hanoi market with 471 sample surveys. Through analyzing the effects of 3 variables which are risk attitude, benefits perception and risks perception to measure attitudes towards the buying life insurance. This research will be useful for improving the way Hanoi people in particular and Vietnamese people in general adopt a positive attitude to life insurance, thereby promoting the intention and behavior to buy products.